Pengaruh Aktivitas Dakwah Bobotoh Taqwa dalam Meningkatkan Keshalehan Sosial - Muhammad Rizki; Bambang Saiful Ma’arif (Jurnal Riset Komunikasi Penyiaran Islam, 2022)
Abstract. This study aims to determine the magnitude of the effect of Bobotoh Taqwa's da'wah activities in increasing social piety. The existence of acts of violence carried out by several Bobotoh elements has an impact on the image of Bobotoh Persib. In the midst of the poor image of Bobotoh among the public, there is Bobotoh Taqwa which aims to make the teachings of Islam the basis for its movement. With Bobotoh Taqwa, this is one way so that people don't just look at Bobotoh one eye. This study uses quantitative methods. The data collection techniques used are questionnaires and interviews. The data analysis technique used is descriptive quantitative including correlation analysis, simple linear regression analysis, coefficient of determination and hypothesis testing. The data were analyzed by descriptive analysis method. The results of the study indicate that Bobotoh Da'wah da'wah activities are very influential on increasing social piety. The effect of da'wah activities in increasing social piety is 78.8%. The effect caused is a positive influence. With the existence of da'wah activities by taqwa, especially in its programs in the social field, it makes a good influence which makes its members more sensitive to social conditions and also indirectly affects individual piety such as always prioritizing worship over other activities such as watching matches Persib. Abstrak. Penelitian ini bertujuan untuk mengetahui besarnya pengaruh aktivitas dakwah Bobotoh Taqwa dalam meningkatkan Keshalehan Sosial. Adanya tindakan kekerasan yang dilakukan oleh beberapa oknum Bobotoh berdampak bagi citra Bobotoh Persib. Ditengah buruknya citra Bobotoh dikalangan masyarakat hadirlah Bobotoh Taqwa yang bertujuan untuk menjadikan ajaran Agama Islam sebagai landasan bergeraknya. Dengan adanya Bobotoh Taqwa ini menjadi salah satu cara agar masyarakat tidak hanya memandang Bobotoh sebelah mata. Penelitian ini menggunakan metode kuantitatif. Adapun teknik pengumpulan data yang digunakan adalah kuesioner dan wawancara. Teknik analisis data yang digunakan adalah deskriptif kuantitatif meliputi analisis korelasi,analisis regresi linear sederhana, koefisien determinasi dan uji hipotesis. Data dianalisa dengan metode deskriptif analisis. Hasil penelitian menunjukkan bahwa kegiatan dakwah Bobotoh Dakwah sangat berpengaruh terhadap peningkatan keshalehan sosial. Pengaruh Aktivitas dakwah dalam meningkatkan keshalehan sosial sebanyak 78.8%. Pengaruh yang ditimbulkan adalah pengaruh positif. Dengan adanya kegiatan dakwah oleh Bobotoh Taqwa terutama dalam program-programnya dibidang sosial membuat pengaruh yang baik yang menjadikan para anggotanya menjadi lebih peka dengan keadaan sosial dan juga secara tidak langsung berpengaruh juga bagi keshalehan individualnya seperti selalu mementingkan ibadah terlebih dahulu dibanding kegiatan lain seperti menonton pertandingan Persib.